Sustainable Competitive Advantage in Indonesia’s Bioethanol Industry: Key Variables and Ecosystem Model - Rachman, Izmirta (PT Mattawang Mediatama Solution, 2025)
The target for bioethanol fuel-grade blending in Indonesia has yet to be achieved, indicating significant barriers to the development of a sustainable industry. This study aims to identify key variables and develop an ecosystem model that supports Sustainable Competitive Advantage (SCA) in the Fuel-Grade Bioethanol Industry (FGBI) in Indonesia. Adopting the Resource-Based View (RBV) and Institutional Theory (IT) approaches, this study analyzes the interaction between internal and external factors influencing industry sustainability. Utilizing an exploratory inductive qualitative method covering the period 2006 to 2024, the research identifies three key RBV variables: (1) demand, (2) raw materials, and (3) technology as well as three coercive IT variables: (1) price formulation, (2) trade structure, and (3) tariffs and incentives as critical elements in achieving SCA. The findings indicate that coercive IT alone is ineffective in achieving SCA without integration with RBV. As both an academic and practical contribution, this study proposes a sustainable ecosystem model for FGBI in Indonesia. Further quantitative testing is needed to examine inter-element dynamics and evaluate the model’s long-term effectiveness. The implications for stakeholders highlight the importance of integrating policy with RBV principles to ensure the sustainability of the industry.